Synthesis and characterization of a novel resin monomer with low viscosity. (April 2017) - Hong, Lihua; Wang, Yu; Wang, Lin; Zhang, Hong; Na, Hui; Zhang, Zhimin
Graphical abstract: Abstract: Objective: In this study, we designed and synthesized a novel macromolecule (tetramethyl bisphenol F acrylate, TMBPF-Ac) with low viscosity, excellent mechanical properties, and good biocompatibility. It could be used as a monomer for dental resin composites, which could reduce the risk of human exposure to bisphenol A derivatives in the oral environment. In addition, the monomer could be used without diluent, thereby avoiding the negative effect of a diluent Methods: TMBPF-Ac was synthesized by a multistep condensation reaction. Its structure was confirmed by 1 H NMR spectra. Different resin mixtures were prepared, and then a number of performance and cytotoxicity tests were performed on these specimens. Results: 1 H NMR spectra showed that the structure of TMBPF-Ac was in accordance with the design. The viscosity of TMBPF-Ac was obviously lower than that of bisphenol-A diglycidyl methacrylate. The three kinds of resins used in this study were in line with ISO 4049:2009 and ISO 10993-5:2009. TMBPF-Ac-based resin had better physical and biological properties.